(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article examines the cultural semantics of lexical units through the lens of lexicographic analysis. The study focuses on how words and expressions reflect the worldview, traditions, and cultural values of a particular linguistic community. Lexicographic methods are used to identify semantic nuances that arise due to cultural differences between languages. Special attention is given to the relationship between language and culture, as well as how cultural connotations are represented in bilingual and explanatory dictionaries. The research highlights the importance of interpreting lexical meaning not only from a linguistic but also from a cultural perspective. The findings contribute to the development of more comprehensive dictionary entries that reflect the cultural depth of lexical units and facilitate intercultural communication.